Pengendalian Persediaan Obat dengan Minimum-Maximum Stock Level di Instalasi Farmasi RSUP Dr. Sardjito Yogyakarta - Titik Rahayu Indarti; Satibi Satibi; Endang Yuniarti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Inappropriate inventory control of medicines in hospital can lead to shortage or over stock, which is a problem faced by Dr. Sardjito Hospital Yogyakarta. The aim of this study was to examine the effect of the Minimum-Maximum Stock Level (MMSL) method on efficiency and effectivity of medicine inventory at Hospital Pharmacy Dr. Sardjito. A quasi experimental nonequivalent without control group design was applied, and purposive sampling was taken from retrospective data in January-June 2018 and the application of methods prospectively i.e. August-December 2018. Thirty-five types of medicines which met the inclusion and exclusion criteria were obtained, i.e. high cost, high volume, clinicaly important, and supply focus. These types of medicines were included in category A of ABC Pareto Analysis. The effect of minimum-maximum stock level method on inventory value, stock out value, and Inventory Turn Over Ratio (ITOR) was analysed using Wilcoxon Signed Rank Test statistic. The effect of minimum-maximum stock level method on stock out incident was analysed using Mc Nemar Test statistic. This study found that minimum-maximum stock level method to impact the positively their efficiency of drug control marked by decreased of inventory value and ITOR ideal value. The effectiveness of drug control marked by decreased incidence of stock out in Hospital Pharmacy Departement Dr. Sardjito.